Unprotected Sex with Injecting Drug Users among Iranian Female Sex Workers: Unhide HIV Risk Study - Khodabakhsh Ahmadi; Majid Rezazade; Mohammad Nafarie; Babak Moazen; Mosaieb Yarmohmmadi Vasel; Shervin Assari (AIDS Research and Treatment)
Purpose. To assess the prevalence and associated factors of unprotected sex with injecting drug users (IDUs) among a sample of female sex workers (FSWs) in Iran. Methods. This cross-sectional study included 144 FSWs who were interviewed as a part of Unhide HIV Risk Study, a national behavioral survey focusing on various high-risk populations, including IDUs, FSWs, and Men who have Sex with Men (MSMs) in 2009. The survey was conducted in eight provinces in Iran using respondent-driven sampling. Participants’ sociodemographic status, HIV knowledge, and HIV attitude were analyzed via logistic regression to determine the predictors of unprotected sex with IDU(s) during the past month. Results. Nineteen percent of FSWs reported at least one occasion of unprotected sex with IDU(s) in the month preceding the study. Higher educational level (OR=−0.653, 95%CI=-1.192 to −0.115), perceived HIV risk (OR=−1.047, 95%CI=-2.076 to −0.019), and perceived family intimacy during childhood (OR=−1.104, 95%CI=-1.957 to −0.251) were all independently associated with lower odds of having unprotected sex with IDU(s) in the month preceding the study. Age, marital status, living condition, HIV knowledge, and perceived behavioral control did not affect the odds of FSWs having sex with IDUs. Conclusion. Perceived HIV risk, which is a modifiable factor, seems to be a promising target for harm reduction interventions amongst Iranian female sex workers. Data presented here may aid in reducing or eliminating the role of sex workers as a bridge for HIV transmission from IDUs to the general population in Iran.